2014
DOI: 10.1212/wnl.0000000000000146
|View full text |Cite|
|
Sign up to set email alerts
|

Naive CD4 T-cell activation identifies MS patients having rapid transition to progressive MS

Abstract: Objective:Our objective was to determine whether altered naive CD4 T-cell biology contributes to development of disease progression in secondary progressive multiple sclerosis (SPMS).Methods:We compared the naive CD4 T-cell gene expression profiles of 19 patients with SPMS and 14 healthy controls (HCs) using a whole-genome microarray approach. We analyzed surface protein expression of critical genes by flow cytometry after T-cell receptor (TCR) stimulation of naive CD4 T cells isolated from HCs and patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…It has been reported that there is enhanced cellular expression of TLR2 in MS patients, e.g. on neutrophils , T cells and in the central nervous system (CNS) . However, in the present study we did not find an enhanced expression of TLR2 on CD14 + monocytes in patients with MS.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that there is enhanced cellular expression of TLR2 in MS patients, e.g. on neutrophils , T cells and in the central nervous system (CNS) . However, in the present study we did not find an enhanced expression of TLR2 on CD14 + monocytes in patients with MS.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, primary progressive (PP) patients and (SP) secondary progressive patients were shown to exhibit a sustained increase in the number of Th1 and T cytotoxic type 1 cells in peripheral blood, suggesting that the progressive phase of the disease is characterized by a permanent peripheral type 1 immune activation . Differences in naive CD4+ T cell biology identify patients with MS having different rates of development of secondary progression ; higher percentages of circulating CD4+ and CD8+ T‐bet T cells were found in SP and PP patients, and these values were correlated with the severity of the disease . Moreover, studies have shown that SP patients display low IFN‐γ, IL‐17 and IL‐10 production, while Th17 activation dominates the immunologic milieu of PP patients .…”
Section: Introductionmentioning
confidence: 99%
“…These authors hypothesize that differential TLRs expression may modulate inflammation and may be associated with MS clinical courses. Increased expression of TLR4 and TLR2 and relative signaling pathways has been described in naïve CD4+ T lymphocytes isolated from secondary progressive MS (SP MS) 21. These authors conclude that SP MS CD4+ T lymphocytes are biologically different from HD in terms of cell activation and this functional disregulation is associated with a subgroup of SP MS patients characterized by a strong response to anti-inflammatory therapies.…”
Section: Discussionmentioning
confidence: 92%